2005
DOI: 10.1158/1078-0432.ccr-04-1684
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 5-Lipoxygenase and Cyclooxygenase 2 in Hamster and Human Oral Cancer and Chemopreventive Effects of Zileuton and Celecoxib

Abstract: Purpose: Previous studies have suggested an important role of aberrant arachidonic acid metabolism, especially the cyclooxygenase (Cox) pathway, in oral carcinogenesis. However, it is unknown whether the 5-lipoxygenase (5-Lox) pathway contributes to oral carcinogenesis, and whether combination of inhibitors of both pathways may have synergistic or additive effects of chemoprevention.Experimental Design: 5-Lox expression was examined in 7,12-dimethylbenz[a]anthracene (DMBA) --induced hamster and human oral canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 40 publications
4
80
0
Order By: Relevance
“…41 More recently, overexpression of LTA 4 H and 5-LOX protein was demonstrated in rat and human esophageal adenocarcinoma 42,43 and hamster and human oral cancer. 44,45 Our data showing overexpression of LTA 4 H protein in lingual lesions/ SCC from ZD rats, as well as in forestomach lesions/SCC from ZD:COX2/2 mice, are consistent with the idea that 5-LOX/ LTA 4 H pathway is of importance in oral carcinogenesis. 45 It is now recognized that NF-jB provides a link between inflammation/immunity and cancer development/progression; and the IjB kinase/NF-jB activation pathway is a target for cancer prevention.…”
Section: Discussionsupporting
confidence: 85%
“…41 More recently, overexpression of LTA 4 H and 5-LOX protein was demonstrated in rat and human esophageal adenocarcinoma 42,43 and hamster and human oral cancer. 44,45 Our data showing overexpression of LTA 4 H protein in lingual lesions/ SCC from ZD rats, as well as in forestomach lesions/SCC from ZD:COX2/2 mice, are consistent with the idea that 5-LOX/ LTA 4 H pathway is of importance in oral carcinogenesis. 45 It is now recognized that NF-jB provides a link between inflammation/immunity and cancer development/progression; and the IjB kinase/NF-jB activation pathway is a target for cancer prevention.…”
Section: Discussionsupporting
confidence: 85%
“…Overexpression of COX2 has been found in human oral cancer and DMBA induced hamster cheek pouch tumor (29,30). In the present study, we found that in tumor samples of Hras128 rats treatment of 4NQO caused a marked increase in the levels of mRNA expression of cyclin D1 and COX2, when compared to the adjacent normal mucosa (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Topical treatment thrice every week for 18 weeks with 3% and 6% zileuton (a specific 5-lipoxygenase inhibitor) reduced the incidence of SCC from 76.9% to 45.8% (P < 0.05) and 32.1% (P < 0.0001) respectively, and treatment with celecoxib 6% to 50% (P < 0.05). The combination of celecoxib 3% with zileuton 3% reduced the SCC incidence to 36% (P < 0.05), suggesting an additive effect of celecoxib and zileuton in the HOCM (37).…”
Section: Discussionmentioning
confidence: 93%
“…In another study (37), hamsters were treated with 0.5% DMBA thrice every week for 6 weeks. Topical treatment thrice every week for 18 weeks with 3% and 6% zileuton (a specific 5-lipoxygenase inhibitor) reduced the incidence of SCC from 76.9% to 45.8% (P < 0.05) and 32.1% (P < 0.0001) respectively, and treatment with celecoxib 6% to 50% (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%